Defining oligometastatic disease from a radiation oncology perspective: An ESTRO-ASTRO consensus document. (July 2020) - Lievens, Yolande; Guckenberger, Matthias; Gomez, Daniel; Hoyer, Morten; Iyengar, Puneeth; Kindts, Isabelle; Méndez Romero, Alejandra; Nevens, Daan; Palma, David; Park, Catherine; Ricardi, Umberto; Scorsetti, Marta; et al.
Highlights: Metastasis-directed radiotherapy (MDRT) has the potential to prolong survival. Definitions and reporting of oligometastatic disease (OMD) are heterogeneous. OMD is typically based on the imaging-detected number of metastases, but definitions in the literature are inconsistent and warrant further study. No formal clinical or molecular biomarkers currently exist to aid classification as OMD. Currently no clinical or molecular biomarkers exist to aid classification of OMD. Advanced technologies are mandatory to guarantee safe MDRT and improve outcome. Consensus for extra-cranial OMD defines maximum 5 metastatic lesions off-protocol. Abstract: Background: Recognizing the rapidly increasing interest and evidence in using metastasis-directed radiotherapy (MDRT) for oligometastatic disease (OMD), ESTRO and ASTRO convened a committee to establish consensus regarding definitions of OMD and define gaps in current evidence. Methods: A systematic literature review focused on curative intent MDRT was performed in Medline, Embase and Cochrane. Subsequent consensus opinion, using a Delphi process, highlighted the current state of evidence and the limitations in the available literature. Results: Available evidence regarding the use of MDRT for OMD mostly derives from retrospective, single-centre series, with significant heterogeneity in patient inclusion criteria, definition of OMD, and outcomes reported. Consensus was reached that OMD is largely independent of primary tumour, metastatic location and the presence or length of a disease-free interval, supporting both synchronous and metachronous OMD. In the absence of clinical data supporting a maximum number of metastases and organs to define OMD, and of validated molecular biomarkers, consensus supported the ability to deliver safe and clinically meaningful radiotherapy with curative intent to all metastatic sites as a minimum requirement for defining OMD in the context of radiotherapy. Systemic therapy induced OMD was identified as a distinct state of OMD. High-resolution imaging to assess and confirm OMD is crucial, including brain imaging when indicated. Minimum common endpoints such as progression-free and overall survival, local control, toxicity and quality-of-life should be reported; uncommon endpoints as deferral of systemic therapy and cost were endorsed. Conclusion: While significant heterogeneity exists in the current OMD definitions in the literature, consensus was reached on multiple key questions. Based on available data, OMD can to date be defined as 1–5 metastatic lesions, a controlled primary tumor being optional, but where all metastatic sites must be safely treatable. Consistent definitions and reporting are warranted and encouraged in ongoing trials and reports generating further evidence to optimize patient benefits.